(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The aim of protecting of all the structural vocabulary of the centers of blood diseases and tumors is to improve the health situation in general and to protect cancer patients and all workers in particular by providing protection and complementary services for the effects of the environment and the internal environment and waste management. "The local literature on these important determinants and determinants in the organization of integrated protection between the inside and outside, "it is be the research problem of this study, to become the goal of this study is "To ensure the protection of all structural vocabulary of the structure of the premises of the centers of blood diseases and tumors of external environmental influences, as well as to ensure the protection of the surrounding environment from the environmental effects of the interior by adopting strict protection systems adopted by global experiences in the configurations of the building “, Selected case study presentts the results of the impact of internal and external environmental protection on blood and tumor centers.